Problems with the Authority of Institutions Handling Corruption Crimes: Challenges and Obstacles in Realizing Peace, Justice, and Strong Institutions in Indonesia - Putra, Samudra Farasi; Wahyudi, Slamet Tri (Rechtsvinding, 2025)
The handling of corruption crimes has become a scourge in Indonesia's law enforcement system. Corruption crimes are extraordinary crimes that must be dealt with through special procedures in separate legal proceedings. In 2002, the government established the Corruption Eradication Commission through Law No. 30 of 2002 on the Corruption Eradication Commission. However, over time, other institutions such as the Attorney General's Office and the Police also gained authority in prosecuting corruption. This has led to legal uncertainty in the prosecution of corruption crimes and has the potential to create overlapping authorities. Meanwhile, Point 16 of the SDGs states that there should be strong state institutions in terms of law enforcement. The research method used is normative juridical with a legislative and conceptual approach. The results and discussion show that the a quo condition of corruption enforcement institutions is still held by three institutions, namely the Corruption Eradication Commission (KPK), the Attorney General's Office of the Republic of Indonesia, and the Indonesian National Police. All three have their own legal basis through Law No. 19 of 2019 concerning Amendments to Law No. 30 of 2002, Law No. 16 of 2004 concerning the Attorney General's Office and its amendments, and Law No. 2 of 2002 concerning the Indonesian National Police and its amendments, all of which grant authority to prosecute criminal acts of corruption. Therefore, the solution to this problem is to abolish the KPK and strengthen the authority of the Attorney General's Office of the Republic of Indonesia because the essential function of the KPK's establishment has been carried out until now, namely as a trigger in the enforcement of criminal acts of corruption in Indonesia, so that its existence is considered irrelevant at this time. This is also in line with point 16 of the SDGs, which requires the strengthening of law enforcement agencies to support the enforcement of the SDGs in Indonesia.